Effect of Green tea Extract on the Quality of Fish Nuggets during Chilled Storage - Jeyakumari, A.; Ninan, George; Visnuvinayagam, S.; Narasimha Murthy, L. (Fishery Technology, 2021)
In the present study, fish nuggets were prepared from pink perch (Nemipterus japonicus) mince and their qualities were evaluated under chilled (2°C) storage. Pink perch mince had 81.46±0.25% moisture, 17.44± 0.20% protein, 0.85±0.05% fat and 1.02±0.02% ash. Fish nuggets were prepared in three different formulations by incorporating corn starch (4%), green tea extract (0.1%) and BHT (0.01%) in to fish mince referred to as: Control, GTE and BHT respectively. Biochemical and microbiological qualities of fish nuggets were evaluated up to 17th day. Results showed an increasing trend in thiobarbituric acid (TBA) values during storage. However, sample containing green tea extract had a lower TBA value (0.34±0.01 to 0.44±0.03 mg MDA kg-1) than BHT incorporated sample (0.42±0.01 to 0.80±0.02 mg MDA/kg) and control (0.82± 0.02 to 2.14±0.01 mg MDA kg-1). Similar trend was also observed for free fatty acids, peroxide value (PV), total volatile base nitrogen (TVB-N) and trimethylamine nitrogen (TMA-N) content. Texture analysis showed an increasing trend in hardness of all samples during storage. L* value showed a decreasing trend in (59.59±1.2 to 56.95±0.95) green tea extract incorporated sample. Based on the sensory and microbial analysis, control had a shelf life of 12 days whereas, products incorporated with green tea extract and BHT had an extended shelf life up to 15 days.